APLIKASI KETAHANAN PANGAN DESA UNTUK ANTISIPASI PANDEMI DENGAN METODE RAD DI CILONGOK - Trias Bratakusuma; Cindy Magnolia (JURNAL REKAYASA INFORMASI, 2021)
One of the problems that will be faced by all countries in the face of a pandemic is the problem of food. A pandemic is a condition in which a disease outbreak occurs globally. Problems in food security are the responsibility of the government and must be considered very seriously. The guarantee of food availability is very important because the impact that this problem can cause will be devastating for various sectors. For example in the health sector, when people do not have enough nutrition and food, their immunity will become weak, causing them to fall ill and catch viruses. One of the efforts to ensure the fulfillment or security of food for the entire community is through food security. In today's digital era, this can be done easily using information technology. Information technology can be implemented more deeply with the Luponas (national online food barn) application with the built-in AI capabilities that will help the government and the public to estimate the amount of food needed in each region and provide subsidies accurately and quickly. The RAD method is using in this application.The Lupomas application is implemented in small government groupings such as at the subdistrict and rural area to facilitate monitoring of community food. Kata Kunci : Luponas (National online food barn), Application Development, Food Sustainability, Pandemic